CRISPR‐Cas9‐mediated efficient directed mutagenesis and RAD51‐dependent and RAD51‐independent gene targeting in the moss Physcomitrella patens. Issue 1 (22nd July 2016) - Collonnier, Cécile; Epert, Aline; Mara, Kostlend; Maclot, François; Guyon‐Debast, Anouchka; Charlot, Florence; White, Charles; Schaefer, Didier G.; Nogué, Fabien
Summary: The ability to address the CRISPR‐Cas9 nuclease complex to any target DNA using customizable single‐guide RNAs has now permitted genome engineering in many species. Here, we report its first successful use in a nonvascular plant, the moss Physcomitrella patens . Single‐guide RNAs (sgRNAs) were designed to target an endogenous reporter gene, PpAPT, whose inactivation confers resistance to 2‐fluoroadenine. Transformation of moss protoplasts with these sgRNAs and the Cas9 coding sequence from Streptococcus pyogenes triggered mutagenesis at the PpAPT target in about 2% of the regenerated plants. Mainly, deletions were observed, most of them resulting from alternative end‐joining (alt‐EJ)‐driven repair. We further demonstrate that, in the presence of a donor DNA sharing sequence homology with the PpAPT gene, most transgene integration events occur by homology‐driven repair (HDR) at the target locus but also that Cas9‐induced double‐strand breaks are repaired with almost equal frequencies by mutagenic illegitimate recombination. Finally, we establish that a significant fraction of HDR‐mediated gene targeting events (30%) is still possible in the absence of PpRAD51 protein, indicating that CRISPR‐induced HDR is only partially mediated by the classical homologous recombination pathway.